KEBIJAKAN REDUKSI INEFISIENSI PEMBIAYAAN PENYELENGGARAAN SEKOLAH DASAR NEGERI (SDN) DAN PENYEDIAAN KECUKUPAN GURU DI KABUPATEN PATI - Suroso Suroso (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2018)
ENGLISHThere are indications of inefficiency in conducting education in Pati Regency. The objectives of the research are: (1) to analyze inefficiency of conducting state slementary schools; and (2) to analyze potential inefficiency of providing teacher adequacy for state elementary schools in the study area.The research uses descriptive approach. The data consist of primary data and secondary ones. Data collecting uses techniques of interview, survey and document observation. The analysis uses descriptive one. There are 4 main findings in the research. Firstly, the provided classrooms based on students of state elementary schools are adequate in the ratio between classrom and students 1 : 21. Secondly, the provided classrooms based on learner-groups of state elementary schools are not adequate in the status shortage 9 classrooms.Thirdly, the provided teachers based on students of state elementary schools are not adequate in the status shortage 56 teachers and the provided teachers based on learner-groups of state elementary schools are not adequate in the status shortage 1.492 teachers.Fourthly, there is a gap between teacher adequacy based on students and teacher adequacy based on learner-groups of state elementary schools namely 1.436 teachers. Assuming the salaries and incentives for a teacher 70 millions Rupiahs, the potential inefficency is approximately 100,520,000,000 Rupiah a year. However, policy for merging state elementary schools should be conducted to improve efficiency of providing teachers and financial education. INDONESIAAda indikasi inefisiensi dalam penyelenggaraan pendidikan di Kabupaten Pati. Penelitian ini memiliki tujuan: (1) menganalisa inefisiensi penyelenggaraan SDN; dan (2) menganalisa potensi inefisiensi penyediaan guru SDN di area studi. Penelitian ini menggunakan pendekatan deskriptif-kuantitatif. Data penelitian meliputi data primer dan data skunder. Pengumpulan data dilakukan dengan menggunakan teknik observasi, wawancara dan survey. Analisis data menggunakan analisis deskriptif. Penelitian ini memiliki 4 temuan utama. Pertama, Standar kecukupan prasarana (ruang kelas) SDN berbasis peserta didik sudah terpenuhi dengan perbandingan ruang kelas terhadap peserta didik sebesar 1 : 21. Kedua, Standar kecukupan prasarana (ruang kelas) SDN berbasis rombel belum terpenuhi dengan kekurangan 9 ruang kelas. Ketiga, Standar kecukupan guru SDN berbasis peserta didik belum terpenuhi dengan status kurang 56 guru dan standar kecukupan guru SDN berbasis rombel belum terpenuhi dengan status kurang 1.492 guru. Keempat, Ada nilai beda batas kecukupan guru SDN berbasis peserta didik dan kecukupan tenaga guru SDN berbasis rombel sebesar 1.436 yang memberikan indikasi potensi inefisiensi. Dengan asumsi gaji dan tunjangan per guru 70 juta per tahun maka ada potensi inefisiensi sebesar Rp. 100.520.000.000 (100,52 milyar rupiah) per tahun. Oleh karena itu, kebijakan rasionalisasi SDN dan normalisasi rombel perlu dilakukan untuk efisiensi guru dan pembiayaan pendidikan.